Creating vector profile graph in ArcGIS Pro based on hiking trail tracking with AllTrails app - Klemen Prah (Dela)
This paper proposes a model for creating a vector profile graph in ArcGIS Pro based on AllTrails tracking. The vector profile graph is important for route’s geometric measurements and spatial analysis in GIS. The model was created in an Excel table, based on the AllTrails output Excel data, and implemented in ArcGIS Pro. A model needed to be equipped with several attributes, including the coordinates of the initial and all other points of the vector profile graph. The same Excel model was also used to create a vector profile graph based on the output of the Stack Profile tool. The two vector profile graphs were compared with each other. Comparison showed significant differences in elevation and surface distance between them. In general, the profile graph created using the Stack Profile tool shows lower elevations and shorter surface distance. This study also points out the issues of positional error that can occur when tracking routes with smartphones, and the discrepancies in creating vector profile graphs using different approaches.